2022
DOI: 10.1002/adfm.202113383
|View full text |Cite
|
Sign up to set email alerts
|

A Light‐Curable and Tunable Extracellular Matrix Hydrogel for In Situ Suture‐Free Corneal Repair

Abstract: Corneal injuries are a major cause of blindness worldwide. To restore corneal integrity and clarity, there is a need for regenerative biointegrating materials for in situ repair and replacement of corneal tissue. Here, light-curable cornea matrix (LC-COMatrix), a tunable material derived from decellularized porcine cornea extracellular matrix containing un-denatured collagen and sulfated glycosaminoglycans is introduced. It is a functionalized hydrogel with proper swelling behavior, biodegradation, and viscosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…AS-OCT characterization showed that the C3H1 and pDCSM-G exhibited similar optical reflectivity as the surrounding corneal stroma, in contrast to HAMA hydrogel. Such observations suggested greater resemblance of the pDCSM-containing hydrogels to the native corneal tissue [ 24 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AS-OCT characterization showed that the C3H1 and pDCSM-G exhibited similar optical reflectivity as the surrounding corneal stroma, in contrast to HAMA hydrogel. Such observations suggested greater resemblance of the pDCSM-containing hydrogels to the native corneal tissue [ 24 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogel derived from decellularized cornea possesses unique advantages in preserving corneal stromal keratocyte cells, facilitating rapid re-epithelialization, and promoting corneal tissue regeneration, which have brought great interests in potential treatments of corneal diseases, especially for corneal wound healing [ 24 , 44 , 54 , 55 ]. However, the dECM hydrogel often suffer from their low mechanical strength and fast degradation, even after chemical crosslinking [ 56 ], which is unsatisfied for long-term repair of corneal defects with critical optical functional (i.e., enough transparency) and tissue regeneration requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To restore intact and clear corneas, bio-integrated materials are also required to repair and replace corneal tissue in situ. Yazdanpanah et al [129] developed a light-curable cornea matrix (LC-COMatrix) bio-integrated material. This is a functionalized hydrogel based on a porcine corneal extracellular matrix and is biodegradable.…”
Section: Regenerative Medicinementioning
confidence: 99%
“…Bio-glue intended for trauma repair are often derived from particular extracellular matrix (ECM) molecules [e.g., fibrin (Kalsi et al, 2017), collagen (Schiele et al, 1992), hyaluronic acid (Luo et al, 2020)], or other natural polymers [e.g., gelatin/alginate (Song et al, 2022), chitosan (Lu et al, 2018)] or synthetic polymers [e.g., cyanoacrylate (Carvalho et al, 2021), polyurethane (Zhao et al, 2021), polyethylene glycol (Privett et al, 2021)]. While both natural and synthetic polymers are widely utilized as tissue adhesives, the use of ECM bio-glue is rarely seen (Nishiguchi and Taguchi, 2021;Yazdanpanah et al, 2022). However, ECM materials used in tissue engineering [e.g., peripheral nerves (Kim et al, 2004), lung (Ohata and Ott, 2020), kidney (Sobreiro-Almeida et al, 2021), liver (Hussein et al, 2020), skin (Wolf et al, 2012)] have shown great prospect.…”
Section: Introductionmentioning
confidence: 99%